1988
DOI: 10.1039/p29880000007
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance spectra of organogermanium compounds. Part 4. Nuclear magnetic resonance spectra and molecular mechanics calculations of germacyclohexane, methylgermacyclohexanes, and dimethylgermacyclohexanes

Abstract: Molecular mechanics calculations in germacyclohexane and methyl-substituted germacyclohexanes reveals that (i) the ring is flattened around the germanium and that (ii) a methyl group on germanium has a slight preference for the axial conformation rather than the equatorial, which is in line with the results for the corresponding silacyclohexanes. The 13C and 73Ge chemical shifts of these germacyclohexanes are consistent with the calculations. Thus, both 13C and 73Ge data indicate that I -m e t h y l -Igermacyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The C---Ge bond lengths [1.929 (5)-1.942 (7) A] are within the range of C(sp3)--Ge bond lengths [1.933 (6)-1.967 (3)A] previously reported for germacyclanes (Faucher, Mazerolles, Jaud & Galy, 1978;Preut, Krcher & Neumann, 1985;Sommese, Cremer, Campbell & Thompson, 1990). All the C---C--C angles (2) (Takeuchi, Shimoda, Tanaka, Tomoda, Ogawa & Suzuki, 1988), except for the bond angle Cring-----Gc ¢-~ for "~ring, which the calculation gave a significantly smaller value (101.9°). This disagreement seems to be reasonable, because the calculation was not carried out for (1) but for (2).…”
Section: C2oh4oge404mentioning
confidence: 69%
See 1 more Smart Citation
“…The C---Ge bond lengths [1.929 (5)-1.942 (7) A] are within the range of C(sp3)--Ge bond lengths [1.933 (6)-1.967 (3)A] previously reported for germacyclanes (Faucher, Mazerolles, Jaud & Galy, 1978;Preut, Krcher & Neumann, 1985;Sommese, Cremer, Campbell & Thompson, 1990). All the C---C--C angles (2) (Takeuchi, Shimoda, Tanaka, Tomoda, Ogawa & Suzuki, 1988), except for the bond angle Cring-----Gc ¢-~ for "~ring, which the calculation gave a significantly smaller value (101.9°). This disagreement seems to be reasonable, because the calculation was not carried out for (1) but for (2).…”
Section: C2oh4oge404mentioning
confidence: 69%
“…1 and 2. There are only relatively minor differences between the two crystal- solution (Takeuchi, Shimoda, Tanaka, Tomoda, Ogawa & Suzuki, 1988). To obtain the precise molecular geometry of the germacyclohexane ring, which is not contained in the Cambridge Structural Database files, we carried out an X-ray crystallographic analysis of the title compound (1) at 142 K.…”
mentioning
confidence: 99%
“…Takeuchi et al published a series of thirteen papers in the 1980s that focused on the 73 Ge NMR of numerous germanes and correlated their spectral data with those of the analogous silicon and tin compounds [48][49][50][60][61][62][63][64][65][66][67][68][69]. Molecular mechanics calculations were also used to further explain the experimental data.…”
Section: Isrn Spectroscopymentioning
confidence: 99%
“…Takeuchi and coworkers prepared a series of methyl and phenyl substituted germacyclohexanes to evaluate conformational preferences of these substituents (Scheme 17) 35,36 . Based on analysis of 13 C NMR spectra and molecular mechanics calculations, they concluded that a C-methyl prefers the equatorial orientation by ca 1.4kcal mol −1 but the Ge-methyl substituent actually shows a slight intrinsic preference for the axial orientation ( Figure 9).…”
Section: B Cyclohexanesmentioning
confidence: 99%
“…Enantioenriched α-alkoxyorganolead compounds have been prepared through lithiation of stannane precursors and trapping of the lithiated species with a triorganolead halide (equation 35) 75 . In the presence of TiCl 4 , these plumbanes add to aldehydes to afford monoprotected syn-1,2-diols.…”
Section: (31)mentioning
confidence: 99%